2003
DOI: 10.1099/jmm.0.05125-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of the hyphal-independent Candida albicans proteinase genes SAP1 and SAP3 in the efg1 mutant is associated with attenuated virulence during infection of oral epithelium

Abstract: The transition of Candida albicans from a yeast to a hyphal form is controlled by several transcriptional factors, including the key regulators Cph1 and Efg1, and is considered an important virulence attribute. These factors, especially Efg1, regulate the expression of hyphal-associated genes e.g. SAP4-SAP6. In order to investigate the relevance of these transcriptional regulators for hyphal-independent SAP genes, recently constructed cph1 and efg1 single mutants and a cph1/ efg1 double mutant lacking these fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 36 publications
7
64
1
Order By: Relevance
“…Each of these attributes was shown to be the result, at least in part, of a premature stop codon in the EFG1 transcription factor gene. It is striking that a clinical strain lacks this key transcriptional regulator given its established role in C. albicans filamentation and virulence (Lo et al 1997;Stoldt et al 1997;Braun and Johnson 2000;Korting et al 2003;Noffz et al 2008). However, loss of EFG1 in P94015 provides a fitness advantage in commensal growth.…”
Section: Mutations Affecting Commensalism and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these attributes was shown to be the result, at least in part, of a premature stop codon in the EFG1 transcription factor gene. It is striking that a clinical strain lacks this key transcriptional regulator given its established role in C. albicans filamentation and virulence (Lo et al 1997;Stoldt et al 1997;Braun and Johnson 2000;Korting et al 2003;Noffz et al 2008). However, loss of EFG1 in P94015 provides a fitness advantage in commensal growth.…”
Section: Mutations Affecting Commensalism and Pathogenesismentioning
confidence: 99%
“…None of the other clinical isolates contained a premature stop mutation in EFG1. In addition to controlling white-opaque switching (Sonneborn et al 1999;Srikantha et al 2000;Zordan et al 2007), EFG1 is a key regulator of filamentous growth and virulence (Lo et al 1997;Stoldt et al 1997;Braun and Johnson 2000;Korting et al 2003;Noffz et al 2008). To test whether the truncated EFG1 gene product in P94015 is functional, we introduced the nonsense mutation into the full-length SC5314 EFG1 allele, generating efg1 STOP .…”
Section: Characterization Of Avirulent Isolate P94015mentioning
confidence: 99%
“…Concomitant with the up-regulation of hyphal wall proteins, the expression of yeast-specific genes such as YWP1 is down-regulated during the yeast-to-hypha transition. Thus, the reduced virulence of the efg1 mutant likely reflects both a lack of expression of hypha-specific genes and a change in the overall organization of the cell wall (155,182). Microarray analysis has further demonstrated that apart from yeast-or hypha-specific genes, Efg1 is also important for the expression of metabolism genes, inducing glycolytic genes and repressing genes essential for oxidative metabolism (81).…”
Section: Vol 71 2007 Signal Transduction Network In C Albicans 357mentioning
confidence: 99%
“…It was shown that the yeast-to-hypha morphogenetic transition promotes escape from macrophages and neutrophils (284,342). Furthermore, dendritic cells are able to differentiate between yeast and hyphal morphotypes, and while both are phagocytosed, this occurs via different receptors and stimulates different immune responses (156).…”
Section: Morphogenesis and Its Association With Virulencementioning
confidence: 99%